2008
DOI: 10.1074/jbc.m708232200
|View full text |Cite
|
Sign up to set email alerts
|

The PHB1/2 Phosphocomplex Is Required for Mitochondrial Homeostasis and Survival of Human T Cells

Abstract: Many immune pathologies are the result of aberrant regulation of T lymphocytes. A functional proteomics approach utilizing two-dimensional gel electrophoresis coupled with mass spectrometry was employed to identify differentially expressed proteins in response to T cell activation. Two members of the prohibitin family of proteins, Phb1 and Phb2, were determined to be up-regulated 4 -5-fold upon activation of primary human T cells. Furthermore, their expression was dependent upon CD3 and CD28 signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 67 publications
7
82
1
Order By: Relevance
“…If the degradation is mediated by ubiquitin as reported, 23 it is possible that the interaction with the core protein interferes with ubiquitin-binding and protects prohibitin from degradation by proteasome. Some posttranslational protein modifications such as phosphorylation are other possible factors for the stabilization, because prohibitin can be serine-phosphorylated 32 ; however, in our examination no serine/threonine/tyrosine phosphorylation of prohibitin was detected in core-expressing cells (data not shown). Thus far, there are no studies showing that prohibitin stabilization leads to a suppressed function as a mitochondrial chaperon.…”
Section: Discussioncontrasting
confidence: 53%
“…If the degradation is mediated by ubiquitin as reported, 23 it is possible that the interaction with the core protein interferes with ubiquitin-binding and protects prohibitin from degradation by proteasome. Some posttranslational protein modifications such as phosphorylation are other possible factors for the stabilization, because prohibitin can be serine-phosphorylated 32 ; however, in our examination no serine/threonine/tyrosine phosphorylation of prohibitin was detected in core-expressing cells (data not shown). Thus far, there are no studies showing that prohibitin stabilization leads to a suppressed function as a mitochondrial chaperon.…”
Section: Discussioncontrasting
confidence: 53%
“…48 In this context it is important to note that PHB has been reported to provide protection against oxidative damage, and we have reported that PHB functions as an iron-binding protein and is involved in mitochondrial iron homeostasis. 47,49 Furthermore, the downregulation of PHB protein level in adipose tissues from ob/ob mice and upregulation of PHB in response to leptin in 3T3-L1 adipocytes further support a role of PHB in adipose tissue homeostasis. Upregulation of PHB by insulin and an inhibitory effect of PHB overexpression on insulin-induced adipogenesis may represent a negative feedback relationship between insulin and PHB to maintain each other's function, and subsequently adipose tissue homeostasis under normal condition.…”
Section: Discussionmentioning
confidence: 87%
“…The PHB1⅐PHB2 phosphocomplex is required for mitochondrial homeostasis and survival of human T cells (47). Insulin-induced phosphorylation of cell membrane PHB1 at tyrosine 114 and 259 by insulin receptor kinase facilitates its interaction with Shp1, which in turn negatively regulates PIP3/Akt signaling in myoblasts (48) and breast cancer cells (48,49).…”
Section: Discussionmentioning
confidence: 99%